2020
DOI: 10.7717/peerj.9701
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic long non-coding RNA-associated competing endogenous RNA network in head and neck squamous cell carcinoma

Abstract: Background This study aimed to develop multi-RNA-based models using a competing endogenous RNA (ceRNA) regulatory network to provide survival risk prediction in head and neck squamous cell carcinoma (HNSCC). Methods All long non-coding RNA (lncRNA), microRNA (miRNA), and mRNA expression data and clinicopathological features related to HNSCC were derived from The Cancer Genome Atlas. Differentially expressed RNAs were calculated using R. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant progress on the pathogenesis of HNSCC has been made in the past decades, the exact molecular mechanisms are still not well understood. Increasing evidences implicates that dysregulation of miRNAs has a critical role in the development and progression of HNSCC (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Meanwhile, SFTA1P also action as competing endogenous RNA in head and neck squamous cell carcinoma. [ 31 ] In hepatocellular carcinoma, AFTA1P could accelerate the tumor proliferation by down regulating mi4766-5p. [ 32 ] Li et al [ 33 ] and Xiong et al [ 34 ] have shown that SFTA1P associated with prognosis and cisplatin chemosensitivity in lung squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%